94.8k views
3 votes
Substitute method. 10=-10x-5y. -7x-14=7y

1 Answer

4 votes

The substitution method involves using the expression of one variable extracted from one equation into the other equation.

We have the equation

- 7 x - 14 = 7 y

which can be easily solved for "y" by dividing both sides by "7" :

- x - 2 = y

Then we can substitute the y variable in the second equation:

so we replace y with (- x - 2) in the other equation as shown below:

10 = - 10 x - 5 y

10 = - 10 x - 5 (- x - 2)

use distributive property to remove the parenthesis:

10 = - 10 x + 5 x + 10

10 = - 5 x + 10

subtract 10 from both sides to isolate the term in "x"

0 = - 5 x

divide bothe sides by "-5"

0 = x

Then x = 0, and we can use this value to solve for "y" in the substitution equation:

y = - x - 2

y = - (0) - 2

y = -2

Then the answer is:

x = 0 and y = - 2

User Saurabh Prajapati
by
5.7k points